Voice QoS in third-generation mobile systems. - Valko, A.G.
We analyze voice quality and system performance in third-generation mobile communication systems. We argue that in these networks that are expected to integrate voice, data, and multimedia services, the transport network can no longer be considered as a lossless transparent traffic channel. Rather, proper dimensioning is needed even for plain voice services. Furthermore, the efficient utilization of the network resources shared by voice and data traffic requires sophisticated traffic management in the statistical multiplexing environment. The contribution of the paper is twofold: first, voice quality in the cellular transport network is analyzed and network dimensioning criteria are derived. Second, building on advances reported in the literature and taking into consideration current standardization activities, a joint performance model is established for the air interface (AI) and the transmission network (TN) allowing for the analysis of end-to-end service performance within a uniform framework. To demonstrate the applicability of this model, we point to some performance problems in the multiservice environment and suggest and evaluate traffic management actions to overcome these
Keywords: CDMA-ATM wideband mobile network; Air interface; Cellular transport network; Data services; End-to-end service performance; Joint performance model; Lossless transparent traffic channel; Multimedia services; Multiservice environment; Network dimensioning; Network resources; Protocols; Standardization activities; Statistical multiplexing; System performance; Third-generation mobile systems; Traffic management; Transmission network; Transport network; Voice QoS; Voice quality; Voice services